Differential impact of COVID-19 school closures on immigrant students: A transnational comparison - Finch, Holmes; Hernández Finch, Maria E.; Avery, Brooke (Frontiers in Education, 2023)
The Covid-19 pandemic had a major impact on many aspects of life, perhaps most notably education. Efforts to mitigate the negative effects of the pandemic, particularly lockdowns, led to major disruptions in schools and resulted in both learning loss and increased mental health challenges for students. These deleterious impacts appear to have been felt most keenly by students from marginalized communities, including first and second generation students. This study sought to investigate the mechanisms underlying these negative effects of pandemic mitigation efforts, particularly in terms of school efforts to support teachers and parents of students not speaking the language of instruction for three nations (Denmark, Russia, and Slovenia) included in the Responses to Educational Disruption Survey (REDS) survey. Results of the study revelated that in Denmark greater school-level support to teachers of non-native language students moderated the relationship between home language status and student perceptions of their relative academic performance before and during the pandemic, but that such was not the case in Russia or Slovenia. Likewise, school-level support to teachers moderated the relationship between home language status and perceived teacher support in Denmark but not in Russia or Slovenia. Implications of these results are discussed.